2007
DOI: 10.1186/1471-2164-8-107
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and functional analysis of the Cation Diffusion Facilitator (CDF) family: improved signature and prediction of substrate specificity

Abstract: Background: The Cation Diffusion Facilitator (CDF) family is a ubiquitous family of heavy metal transporters. Much interest in this family has focused on implications for human health and bioremediation. In this work a broad phylogenetic study has been undertaken which, considered in the context of the functional characteristics of some fully characterised CDF transporters, has aimed at identifying molecular determinants of substrate selectivity and at suggesting metal specificity for newly identified CDF tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
441
2
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 372 publications
(474 citation statements)
references
References 57 publications
23
441
2
8
Order By: Relevance
“…Whereas MamP was implicated in the control of magnetite crystal size and number, MamE is thought to be involved in magnetosome formation by directing the proper localization of a subset of magnetosome proteins (10). MamM and MamB share homology with cation diffusion facilitator (CDF) transporters (34,35) and are assumed to mediate iron transport into the magnetosome compartment (8). Multiple sequence comparisons were performed with all identified Mam homologs of Mbav to analyze their phylogenetic relation to magnetosome proteins from other MTB (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas MamP was implicated in the control of magnetite crystal size and number, MamE is thought to be involved in magnetosome formation by directing the proper localization of a subset of magnetosome proteins (10). MamM and MamB share homology with cation diffusion facilitator (CDF) transporters (34,35) and are assumed to mediate iron transport into the magnetosome compartment (8). Multiple sequence comparisons were performed with all identified Mam homologs of Mbav to analyze their phylogenetic relation to magnetosome proteins from other MTB (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The Two Conserved Hydrophilic Amino Acid Residues in TMs II and V of hZnT6 Are Not Involved in the Zinc-binding SiteMany CDF/ZnT proteins form homo-oligomers with the zincbinding site being formed by four conserved hydrophilic residues (2ϫ Asp and 2ϫ His in vertebrates) present in TMs II and V (12,23) (Fig. 1).…”
Section: Znt6mentioning
confidence: 99%
“…Information obtained from a number of mutagenesis studies has shown that the zinc-binding site embedded in the TM domains (TMDs) is essential for zinc transport across the cellular membrane by the CDF/ZnT proteins, suggesting that this may be true for all of the CDF/ZnT homo-oligomers (reviewed in Ref. 23).…”
mentioning
confidence: 99%
“…This protein increased Mn tolerance and accumulation when expressed in yeast or Arabidopsis (13). The CDF gene family is phylogenetically very widely distributed with representatives in bacteria, yeast, plants, and humans (20,21). The encoded transporters are powered by H ϩ or K ϩ antiport (22).…”
mentioning
confidence: 99%